Critical Legal Reading: The Elements, Strategies and Dispositions Needed to Master this Essential Skill - Alex Steel; Kate Galloway; Mary Heath; Natalie Skead (Legal Education Review)
[Extract} The hypothesis that the university academic must have both a research and a teaching component to their work is under attack. At one stage it would have been said that every academic is by definition a researcher – that a research component is fundamental to the ethos of a tertiary institution and, specifically, the development of the teaching criteria for assessment and the setting of levels within that assessment. After all, how could one be comfortable that the grade for a particular piece of work was set at the appropriate level unless the assessor was knowledgeable in the research area? How could a marker confidently conclude that a student has applied the law correctly to a problem based scenario if they were not an active researcher in the relevant area of law? Universities were not to be seen as a college of teaching experts, but as experts teaching and disseminating the fruits of their research labour. It was the research component that allowed an institution to be its own benchmark and standard setter.